O oficial-alternativo: interfaces entre o discurso das protagonistas das mudanças e o discurso da escola plural - Glaucia Conceicao Carneiro (2002)
This Investigation analyzed the interfaces between the conditions of production of the speech of change of the Plural School and the speech of some of the considered teachers producing of the significant experiences happened in the beginning of the nineties in the Belo Horizonte in the official document of the proposal. We looked goes, then, to evidence the logic of the process that involved the selection and the institutionalization certain discursive formations of the educational field in detriment of other. Our work integrates three parts relatively autonomous in spite of inter-relate-if. In the first part of this work we tried to build a picture of references to recover, among other aspects the bases of the social epistemology of the current speeches of educational change and that, also, it allowed to interrogate us certain justifications of some of the current change rhetorics. In the second it leaves we tried to understand the process of production of the speech of educational change, through inclusion, produced by Plural School, that he became important the System of Education of Belo Horizonte lifting adds aspects related with the type of established discursive contract it goes the document-proposal. We identified in the "official-alternative" speech, produced by Plural School certain thematic courses or adds implicit ones that end up determining the type of protocol alone that your reading becomes effective to your possible speakers. The third part of our study was an attempt of investigating the following subject better: since document-proposed he affirms him that Plural School "was born" of the practice of adds teachers it would be interesting to try to know them better. It was what tried to of the to captures, through interview, the speeches of adds teachers of who Plural School i placed the spokesperson and to confront them with the official speech. The "Analysis of the Speech" was used the main theory and methodology of analysis of the dates of this investigation. The results demonstrated that needed to be attentive if we want to avoid the illusion that the ethnocentrism of the speech of the traditional pedagogues and your contempt goes the knot-academic cultures, the well the your goes the diversity can be corrected easily, by the speech of the application of the innovative pedagogues. It necessary, therefore, to go besides this establishes between the tradition and the